1985
DOI: 10.1111/j.1365-246x.1985.tb05131.x
|View full text |Cite
|
Sign up to set email alerts
|

Methodologies for estimating t*(f) from short-period body waves and regional variations of t*(f) in the United States

Abstract: In this paper we discuss some aspects of estimating t* from shortperiod body waves and present some limits on t* ( f ) models for the central and south-western United States (CUS and SWUS). We find that for shortperiod data, with frequencies above 1 or 2Hz, while the average spectral shape is stable, the smaller details of the spectra are not; thus, only an average t*, and not a frequency-dependent t*, can be derived from such information. Also, amplitudes are extremely variable for short-period data, and thus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
0

Year Published

1986
1986
2011
2011

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 23 publications
3
38
0
Order By: Relevance
“…Across a broad range of surface-and body-wave frequencies from *0.01 to *100 Hz (e.g., DER et al, 1982DER et al, , 1986LEES et al, 1986;ABERCROMBIE, 1998), Q values consistently increase with frequency in a vast majority of observations. However, attenuation is also always measured indirectly and in the background of strong amplitude variations, and the difficulty of differentiating its apparent attributes from the true in situ properties is well known (DER and LEES, 1985;WHITE, 1992). Predominant observations of positive Q(f) dependencies often reaching and exceeding the linear Q µ f rate still suggest serious concerns about the measurement and interpretation methodology.…”
Section: Introductionmentioning
confidence: 99%
“…Across a broad range of surface-and body-wave frequencies from *0.01 to *100 Hz (e.g., DER et al, 1982DER et al, , 1986LEES et al, 1986;ABERCROMBIE, 1998), Q values consistently increase with frequency in a vast majority of observations. However, attenuation is also always measured indirectly and in the background of strong amplitude variations, and the difficulty of differentiating its apparent attributes from the true in situ properties is well known (DER and LEES, 1985;WHITE, 1992). Predominant observations of positive Q(f) dependencies often reaching and exceeding the linear Q µ f rate still suggest serious concerns about the measurement and interpretation methodology.…”
Section: Introductionmentioning
confidence: 99%
“…1982a;Der & Lees 1985). In the western Pacific, Sipkin &Jordan (1979) have found that multiple ScS waves required a frequency dependence of Q.…”
mentioning
confidence: 96%
“…Spectral domain measures of intrinsic attenuation such as t * ( f ) (see Der & Lees 1985) that use average spectral shapes should systematically yield lower intrinsic attenuation estimates than time domain estimates of attenuation from the initial P-wave rise time. The spectral estimate of the high-frequency content of the waveform contains the delayed highfrequency energy while the P-wave rise time relies only upon the earliest arriving P-wave energy.…”
Section: Discussionmentioning
confidence: 99%